2006
DOI: 10.1097/01.jnen.0000235119.52311.16
|View full text |Cite
|
Sign up to set email alerts
|

Dysferlin Is a New Marker for Leaky Brain Blood Vessels in Multiple Sclerosis

Abstract: Dysferlin is a muscle protein involved in cell membrane repair and its deficiency is associated with muscular dystrophy. We describe that dysferlin is also expressed in leaky endothelial cells. In the normal central nervous system (CNS), dysferlin is only present in endothelial cells of circumventricular organs. In the inflamed CNS of patients with multiple sclerosis (MS) or in animals with experimental autoimmune encephalomyelitis, dysferlin reactivity is induced in endothelial cells and the expression is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 52 publications
7
97
0
3
Order By: Relevance
“…Subtraction techniques or quantification of SI variations of CSF on FLAIR images obtained after contrast injection might be necessary when investigating patients affected by diseases that at some stages are characterized by subtle, diffuse BBB leakage. For example these postanalysis steps could be useful in advanced, chronic stages of multiple sclerosis, in which the conventional MR technique (i.e., contrast-enhanced T 1 -weighted images) might only par- tially detect neuropathologically evident BBB disturbance (12).…”
Section: Resultsmentioning
confidence: 99%
“…Subtraction techniques or quantification of SI variations of CSF on FLAIR images obtained after contrast injection might be necessary when investigating patients affected by diseases that at some stages are characterized by subtle, diffuse BBB leakage. For example these postanalysis steps could be useful in advanced, chronic stages of multiple sclerosis, in which the conventional MR technique (i.e., contrast-enhanced T 1 -weighted images) might only par- tially detect neuropathologically evident BBB disturbance (12).…”
Section: Resultsmentioning
confidence: 99%
“…While clinical disease is highly variable between patients with relapsing MS, the clinical course of the disease is surprisingly uniform in patients who have entered the progressive phase. Furthermore, onset of steady disease progression, both in patients with primary or secondary progressive disease, occurs around the same age (age [40][41][42][43][44][45][46][47][48][49][50], irrespective of previous disease severity or course [21,22].…”
Section: Oxidative Damage In Ms Lesionsmentioning
confidence: 99%
“…Studies have reported leakage of serum proteins outside discrete areas of demyelination and inflammation, 19,20 as well as subtle blood-brain barrier disruption in nonenhancing lesions. 21 However, 3 factors render this explanation unlikely: 1) intralesional veins, where this effect should be most prominent, were narrowed rather than enlarged; 2) veins within actively enhancing lesions, where the blood-brain barrier is most widely open, did not further narrow once the contrast enhancement resolved; and 3) images were acquired during injection of gadolinium, so subtle leakage, which is likely to be slow, should only have a minor effect on apparent diameter.…”
Section: Ms Vs Non-ms Veinsmentioning
confidence: 99%